The American Health Care System A Practical Guide for Foreign Medical Graduates Who Want to Enter the System (Springer International Publishing, 2018)
This book collates the expertise and experience of leading medical professionals to give foreign medical graduates an understanding of the American health care system. All the fundamental stages in the preparation of a foreign medical graduate for medical training in the US are covered. The book aims to provide essential information and guidance on how to navigate the American health care system. The characteristics of it are described in this concise and easy to read volume to help foreign medical graduates integrate into the American system.